Presidential Threshold Concept in the Democratic Perspective in Indonesia (International Journal of Scientific Research and Management (IJSRM), 2019)
This study aims to analyze the Presidential Threshold Concept in the Democratic Perspective in Indonesia. This is because democracy currently applies the principle of popular sovereignty where the highest government is in the hands of the people in this case the people are the source of the power of a country. The concept of PT is not in accordance with the aims and objectives of democracy. This research is a normative study with a legal approach, conceptual approach, and historical approach. Based on the results of the study concluded that it is known that the Democratic System, and the determination of the Presidential Threshold in this presidential election have violated democratic values, do not provide a sense of justice in a democratic party. Presidential systems, basing presidential elections on legislative election results is an anomaly. Because, the legitimacy basis of a president in a presidential system scheme is not determined by parliamentary political formation resulting from legislative elections. Presidential institutions and parliaments in presidential systems are two separate institutions that have different legitimacy bases.